1995
DOI: 10.1002/1097-0142(19950101)75:1<34::aid-cncr2820750108>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized, doúble-blind, multiinstitutional trial of vaccinia melanoma oncolysate-active specific immunotherapy for patients with stage II melanoma

Abstract: Background. In a Phase II trial, surgical adjuvant active specific immunotherapy using a live vaccinia virus‐augmented allogeneic polyvalent melanoma cell lysate, vaccinia melanoma oncolysate (VMO), produced a significant disease free interval (DFI) in patients with International Union Against Cancer Stage II melanoma with positive lymph nodes. Therefore, a Phase III randomized prospective, double‐blind, multiinstitutional, surgical adjuvant VMO trial was performed to determine the efficacy of VMO to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…For the validity of such a comparison, nearly identical patients in the compared cadres are needed. In patients with stage III melanoma, active "tumor-specific" immunization with vaccinia viral oncolysates yielded slightly better results than direct oncolysis induced by vaccinia virus injected into the patients [155,201,370,[436][437][438]. The hope for the success of virotherapy with naturally oncolytic viruses for human cancers rests on the fact that both immunization with viral oncolysates prepared ex vivo and viral oncolysis accomplished in vivo induce specific postoncolytic anti-tumor immunity [213,234,358,372].…”
Section: Concluding Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the validity of such a comparison, nearly identical patients in the compared cadres are needed. In patients with stage III melanoma, active "tumor-specific" immunization with vaccinia viral oncolysates yielded slightly better results than direct oncolysis induced by vaccinia virus injected into the patients [155,201,370,[436][437][438]. The hope for the success of virotherapy with naturally oncolytic viruses for human cancers rests on the fact that both immunization with viral oncolysates prepared ex vivo and viral oncolysis accomplished in vivo induce specific postoncolytic anti-tumor immunity [213,234,358,372].…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Nevertheless, this clinical trial inadvertently showed a favorable trend for MVO immunotherapy over direct VV oncolysis. In comparison with surgically treated control groups of several other prominent clinical trials (testing IFN-α or IFN-γ against surgically treated controls), the VMO and the VV groups together and the VV group in itself performed better than the surgically treated control groups [201,[435][436][437][438]. Thus, in the VV group, live vaccinia virus exerted some oncolytic effect, but less than the VMO.…”
Section: The Wistar Institute's Vaccinia Viral Oncolysatementioning
confidence: 99%
See 1 more Smart Citation
“…Both peptide and tumor lysate-loaded dendritic cells have been previously utilized to vaccinate patients. [43][44][45][46][47][48][49] A preferred method to manufacture such a hybrid uses un-cultured, post-irradiation, tumor cells to produce a non-proliferative hybrid cell or dendritoma that retains both the character of the tumor cells in addition to the ability to act as an effective APC. Animal studies have shown these hybrid cells capable of producing an anti-tumor specific immune response.…”
Section: Dendritic Cell Vaccinementioning
confidence: 99%
“…However, convincing therapeutic efficacy has not yet been demonstrated in prospective randomized trials. [7] Early efforts to evaluate responses to tumor vaccines focused on humoral responses. The result was the identification of many antigens that could be defined serologically on melanoma cells, including glycoproteins and gangliosides.…”
Section: Experience With Tumor Vaccinesmentioning
confidence: 99%